2020
DOI: 10.1021/acscatal.0c02320
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Hydrogenation of Fatty Acids on Cu/ZrO2: Demystifying the Role of Carrier Structure and Metal–Support Interface

Abstract: The catalytic transformation of renewable fatty acids into value-added fatty alcohols without the use of gaseous hydrogen is a versatile technique for the utilization of microalgae and waste cooking oil, where Cu-based catalysts are considered to be the most suitable candidate. However, the interpretation of the structure–reactivity relationship caused by different crystal types of carriers and the metal–support interface is not well understood. Herein we synthesized ZrO2-supported Cu nanoparticle catalysts vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 38 publications
(67 reference statements)
3
35
0
1
Order By: Relevance
“…4a and Figure S17a), which con rmed that isolated Cu 1 -O 3 active sites in Cu/ZrO 2 were really stable. However, the local Cu particles with 0.21nm spacing for Cu (111) planes 15,48,50,51 detected in used CAZ-15 by HRTEM (Fig. 4b, Figure S17b) revealed that Cu species were partially aggregated and reduced during the catalytic process, consistent with the XPS results (Fig.…”
Section: Resultssupporting
confidence: 82%
“…4a and Figure S17a), which con rmed that isolated Cu 1 -O 3 active sites in Cu/ZrO 2 were really stable. However, the local Cu particles with 0.21nm spacing for Cu (111) planes 15,48,50,51 detected in used CAZ-15 by HRTEM (Fig. 4b, Figure S17b) revealed that Cu species were partially aggregated and reduced during the catalytic process, consistent with the XPS results (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Based on the source of the hydrogen, the FAL-to-FOL process can be broadly classified into two categories: conventional hydrogenation using molecular H 2 and transfer hydrogenation reaction consuming organic compounds as the hydrogen source ( Valekar et al., 2020 ; Gong et al., 2017 ). Although Cu-based catalysts are commonly used in both hydrogenation systems, the transfer hydrogenation process with the use of methanol, ethanol, 2-propanol, or formic acid as the hydrogen donor has yielded more promising prospect ( Zhang et al., 2018a , 2018b , 2020 ; Villaverde et al., 2015 ; Qiu et al., 2020 ; Du et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the acidity of the fatty acid resulted in a significant metal loss, together with the high cost of noble and rare-earth metals, earth-abundant metals with lower cost are required. Thus, Cu-based catalysts are often used in the selective HDO of fatty acid because of the satisfactory selectivity to alcohols, and the introduction of Fe, Zn, and Zr improves the activity. And the search for an efficient and inexpensive catalyst for the selective HDO of fatty acid is still ongoing.…”
Section: Introductionmentioning
confidence: 99%